Prospective, historically controlled study to evaluate the efficacy and safety of a new paediatric formulation of nifurtimox in children aged 0 to 17 years with Chagas disease one year after treatment (CHICO) - Altcheh, Jaime; Castro, Luis; Dib, Juan C.; Grossmann, Ulrike; Huang, Erya; Moscatelli, Guillermo; Pinto Rocha, Jimy José; Ramírez, Teresa Estela; on behalf of the CHICO Study Group (PLOS Neglected Tropical Diseases, 2021)
Author summary New cases of Chagas disease, which is caused by infection with the protozoan parasite Trypanosoma cruzi, mostly occur in children. Undiagnosed, or without effective treatment following diagnosis, the infection will persist. Around a third of those with chronic Chagas disease will develop serious disorders, such as heart or digestive system disease. Thus, early effective treatment is important to eliminate the parasite. In this prospective study, we used divisible, dispersible formulations of nifurtimox in 30 mg and 120 mg tablets to treat patients aged from newborn to 17 years with age- and weight-adjusted doses for 60 days or for 30 days plus placebo for 30 days. After 12 months, we found serological response rates of 33% and 19% of children in the 60-day and 30-day treatment groups, respectively. The proportion of patients with parasite detectable in blood by polymerase chain reaction tests also decreased substantially with both treatments during this period. Nifurtimox was safe and well tolerated in paediatric patients. The study continues and will provide long-term data from follow-up of 4 years after end of nifurtimox treatment.